101 facets of Taman Negara : a royalty-free image collection cd-rom - Loo, Soon Meng (Kuala Lumpur : MacWorld Sdn. Bhd., 1998)
This interactive CD-ROM presents a gallery of the beauty of nature, a testimony to the wonders of tropical nature-close up and at a distance
Executive producer, Chin Peck Heng ; photographers, Chin Paik Chang, Teo Gow, Tang Siew Fong
Narrator: Leonard M. Fernando
Narrator: Loo Soon Meng
System requirements: Windows 95 with 16MB RAM, super VGA, sound blaster or compatible sound card, double speed CD-ROM drive or higher
Keywords: Taman Negara (Malaysia).; National parks and reserves -- Malaysia; Nature conservation -- Malaysia